KONSEP PENDIDIKAN ISLAM TRANSDISIPLINER: INTEGRASI ILMU, NILAI, DAN TEKNOLOGI DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - Jatmiko, Tri Budi; Wahyuni, Sri (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
Global changes marked by technological disruption, value crises, and social complexity demand a more integrative and adaptive paradigm in Islamic education. Transdisciplinary Islamic education is offered as a solution that unites knowledge, values, and technology within the framework of Islamic philosophy. This study, through a literature review using a hermeneutic-philosophical approach, formulates the concept both philosophically and applicatively. The results show that transdisciplinary Islamic education is holistic, integrating spiritual, intellectual, and social dimensions; ontologically, it acknowledges the unity of the physical and metaphysical; epistemologically, it incorporates the bayani, burhani, irfani, and tajribi methods; and axiologically, it balances divine and human values. Technology is positioned as a strategic medium for integrating knowledge and values. The implementation model includes institutional reform, thematic-integrative curriculum, problem-based learning, and holistic evaluation. In conclusion, transdisciplinary Islamic education serves not merely as a vehicle for knowledge transfer but as a driver of social transformation and sustainable civilizational development. The study recommends cross-sector collaboration and the development of transdisciplinary competencies among educators as strategic steps for implementation in Islamic educational institutions in Indonesia.